(3QhVI GdWGdHjf hYeOI GdeJbjfs - (3jMji Hf TQa Hf eQj Hf MSf GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjG, eMjj GdOjf, (B676 (3g` s; (3YHO GdcQje Hf eMeO Hf YHO GdcQje, CHh GdbGSe GdQGaYj GdbRhjfj,J (B623 (3g` s
(3ChdgG (B:s
(3cJGH YTQI GdfSGA hGdbSe hGdTbGb s
(3BNQgG (B:s
(3aQY eGdG QhM ajg cGdYbO hGdbfi hGdQhM s
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B55 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B3s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B2003 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B11 - (3U (B304 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B929s
Keywords: (3Gdabg GdTGaYjs